Performing Environmentalisms : Expressive Culture and Ecological Change - Tuohy, Sue; Dirksen, Rebecca; Borland, Katherine; McDowell, John Holmes, 1946- (Book collections on Project MUSE., 2021)
"Performing Environmentalisms examines the existential challenge of the twenty-first century: improving the prospects for maintaining life on our planet. The contributors focus on the strategic use of traditional artistic expression--storytelling and songs, crafted objects, and ceremonies and rituals--performed during the social turmoil provoked by environmental degradation and ecological collapse. Highlighting alternative visions of what it means to be human, the authors place performance at the center of people's responses to the crises. Such expression reinforces the agency of human beings as they work, independently and together, to address ecological dilemmas. The essays add these people's critical perspectives--gained through intimate struggle with life-altering force--to the global dialogue surrounding humanity's response to climate change, threats to biocultural diversity, and environmental catastrophe. Interdisciplinary in approach and wide-ranging in scope, Performing Environmentalisms is an engaging look at the merger of cultural expression and environmental action on the front lines of today's global emergency"--